Finnish pre-service teachers’ knowledge about the Indigenous Sámi people - Korte, Satu-Maarit; Paksuniemi, Merja; Keskitalo, Pigga; Selkälä, Arto; Körkkö, Minna; Anderson, Kirk; Sarivaara, Erika; Joona, Tanja (Diaspora, Indigenous, and Minority Education, 2024)
Teacher education worldwide struggles to prepare pre-service teachers for increasingly diverse teaching contexts, and for such preparation, it is imperative to understand their prior knowledge and attitudes. This study surveyed pre-service teacher students in their first study year in a Northern Finnish teacher education program to determine the knowledge they had about the indigenous Sámi people and their evaluation of their own competency in this regard. The study is based on data collected from a web survey conducted during 2018–2020 (n = 176). The data analysis was conducted using Fisher’s exact test and the Pearson chi-squared test. The findings indicate that even though the pre-service teachers had some varying prior knowledge of the Sámi people, to fulfil the requirements set by the National Board of Education, the challenge is to provide teaching on the national cultures of Finland according to the requirements of culturally responsive teaching (CRT). Teacher education worldwide faces challenges in preparing prospective teachers for diverse classrooms. Understanding pre-service teachers’ knowledge and attitudes toward diversity is crucial for achieving this goal. This article details a study surveying first-year pre-service teachers at a Finnish university to evaluate their knowledge of and attitudes toward the Indigenous Sámi people. A web survey (n = 172) was used to collect the data. The data analysis was conducted using Fisher’s exact test and the Pearson chi-squared test. The findings indicate that although the pre-service teachers had some prior knowledge of the Sámi people, there is a need for culturally responsive education (CRE) that meets the Finnish National Board of Education’s standards for teaching about national cultures. The insights derived from this study offer clear directives for fostering inclusive teacher education practices that address the diverse needs of students from Indigenous and multicultural backgrounds.